The AMP-Dependent Protein Kinase (AMPK) Activator A-769662 Causes Arterial Relaxation by Reducing Cytosolic Free Calcium Independently of an Increase in AMPK Phosphorylation - Huang, Yi; Smith, Corey A.; Chen, Grace; Sharma, Bharti; Miner, Amy S.; Barbee, Robert W.; Ratz, Paul H. (Frontiers in Pharmacology, 2017)
Although recent studies reveal that activation of the metabolic and Ca2+ sensor AMPK strongly inhibits smooth muscle contraction, there is a paucity of information about the potential linkage between pharmacological AMPK activation and vascular smooth muscle (VSM) contraction regulation. Our aim was to test the general hypothesis that the allosteric AMPK activator A-769662 causes VSM relaxation via inhibition of contractile protein activation, and to specifically determine which activation mechanism(s) is(are) affected. The ability of A-769662 to cause endothelium-independent relaxation of contractions induced by several contractile stimuli was examined in large and small musculocutaneous and visceral rabbit arteries. For comparison, the structurally dissimilar AMPK activators metformin (MET), simvastatin (SIM), and berberine (BBR) were assessed. A-769662 displayed artery- and agonist-dependent differential inhibitory activities that depended on artery size and location. A-769662 did not increase AMPK-pT172 levels, but did increase phosphorylation of the downstream AMPK substrate, acetyl-CoA carboxylase (ACC). A-769662 did not inhibit basal phosphorylation levels of several contractile protein regulatory proteins, and did not alter the activation state of rhoA. A-769662 did not inhibit Ca2+- and GTPS-induced contractions in  escin-permeabilized muscle, suggesting that A-769662 must act by inhibiting Ca2+ signaling. In intact artery, A-769662 immediately reduced basal intracellular free calcium ([Ca2+]i), inhibited a stimulus-induced increase in [Ca2+]i, and inhibited a cyclopiazonic acid (CPA)-induced contraction. MET increased AMPK-pT172, and caused neither inhibition of contraction nor inhibition of [Ca2+]i. Together, these data support the hypothesis that the differential inhibition of stimulus-induced arterial contractions by A-769662 was due to selective inhibition of a Ca2+ mobilization pathway, possibly involving CPA-dependent Ca2+ entry via an AMPK-independent pathway. That MET activated AMPK without causing arterial relaxation suggests that AMPK activation does not necessarily cause VSM relaxation.